1993
DOI: 10.1111/j.1469-8137.1993.tb03768.x
|View full text |Cite
|
Sign up to set email alerts
|

Abscission in leaf and fruit explants of Prunus persica (L.) Batsch

Abstract: SUMMARYStructural and enzymatic aspects of leaf and fruit abscission in explants treated with exogenous ethylene were studied and compared with those previously observed under field conditions. Light and electron microscopy observations reconfirm that differences in abscission occur in leaf and fruit, and in explants cell separation is accelerated, with a more dramatic degradation of the cell walls. In fruit, digestion starts from the middle lamella, and subsequently extends to the entire parietal mass. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Previous studies showed that in fruits at a late growtb stage, this abscission zone can be morpbologically distinguished from the surrounding tissues due to its small sized cells and the very few intercellular spaces (Rascio et al, 1985;Zanchin et al, 1993). Therefore, as generally considered for the morphologically predifferentiated abscission zones (Sexton & Roberts, 1982;, it is plausible to regard this morphological predifferentiation as a prerequisite necessary to the AZ3 cells for the acquisition of sensitivity to the abscission stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies showed that in fruits at a late growtb stage, this abscission zone can be morpbologically distinguished from the surrounding tissues due to its small sized cells and the very few intercellular spaces (Rascio et al, 1985;Zanchin et al, 1993). Therefore, as generally considered for the morphologically predifferentiated abscission zones (Sexton & Roberts, 1982;, it is plausible to regard this morphological predifferentiation as a prerequisite necessary to the AZ3 cells for the acquisition of sensitivity to the abscission stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The two cell separation modes, whicb coincide with tbose already observed in leaf AZ and fruit AZ3 (Zanchin et al, 1993), might actually be the modes of response to abscission stimuli of the plant vegetative and reproductive bodies, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations